A new species of Oxytropis (Fabaceae) from Central Apennines (Italy) - Conti, Fabio; Pennesi, Riccardo; Uzunov, Dimitar; Bracchetti, Luca; Bartolucci, Fabrizio (Phytotaxa, 2018)
A new species, Oxytropis ocrensis, is described from Central Apennines (Italy). This species is morphologically closely related to O. halleri group (O. xerophila, O. halleri and O. korabensis) occurring in the Alps and Albania, from which it differs by longer calyx, larger lateral calyx teeth, long hairs on calyx teeth, smaller keel limb and larger diameter of stem under the inflorescence. The taxonomic relationships of the new species with the hitherto known species of O. halleri group are examined and discussed.